COVID‐19 in kidney transplant recipients: A multicenter experience in Istanbul. Issue 5 (13th July 2020) - Demir, Erol; Uyar, Murathan; Parmaksiz, Ergun; Sinangil, Ayse; Yelken, Berna; Dirim, Ahmet Burak; Merhametsiz, Ozgur; Yadigar, Serap; Atan Ucar, Zuhal; Ucar, Ali Riza; Demir, Mehmet Emin; Mese, Meral; et al.
Abstract: Introduction: Management of COVID‐19 in kidney transplant recipients should include treatment of the infection, regulation of immunosuppression, and supportive therapy. However, there is no consensus on this issue yet. This study aimed to our experiences with kidney transplant recipients diagnosed with COVID‐19. Material and Methods: Kidney transplant recipients diagnosed with COVID‐19 from five major transplant centers in Istanbul, Turkey, were included in this retrospective cohort study. Patients were classified as having moderate or severe pneumonia for the analysis. The primary endpoint was all‐cause mortality. The secondary endpoints were acute kidney injury, the average length of hospital stay, admission to intensive care, and mechanical ventilation. Results: Forty patients were reviewed retrospectively over a follow‐up period of 32 days after being diagnosed with COVID‐19. Cough, fever, and dyspnea were the most frequent symptoms in all patients. The frequency of previous induction and rejection therapy was significantly higher in the group with severe pneumonia compared to the moderate pneumonia group. None of the patients using cyclosporine A developed severe pneumonia. Five patients died during follow‐up in the intensive care unit. None of the patients developed graft loss during follow‐up. Discussion: COVID‐19 has been seen to more commonly cause moderate or severe pneumonia in kidney transplant recipients. Immunosuppression should be carefully reduced in these patients. Induction therapy with lymphocyte‐depleting agents should be carefully avoided in kidney transplant recipients during the pandemic period.